From lithium to sodium: cell chemistry of room temperature sodium–air and sodium–sulfur batteries - Adelhelm, Philipp; Hartmann, Pascal; Bender, Conrad L; Busche, Martin; Eufinger, Christine; Janek, Juergen (Beilstein journal of nanotechnology, 2015)
Research devoted to room temperature lithium–sulfur (Li/S 8 ) and lithium–oxygen (Li/O 2 ) batteries has significantly increased over the past ten years. The race to develop such cell systems is mainly motivated by the very high theoretical energy density and the abundance of sulfur and oxygen. The cell chemistry, however, is complex, and progress toward practical device development remains hampered by some fundamental key issues, which are currently being tackled by numerous approaches. Quite surprisingly, not much is known about the analogous sodium-based battery systems, although the already commercialized, high-temperature Na/S 8 and Na/NiCl 2 batteries suggest that a rechargeable battery based on sodium is feasible on a large scale. Moreover, the natural abundance of sodium is an attractive benefit for the development of batteries based on low cost components. This review provides a summary of the state-of-the-art knowledge on lithium–sulfur and lithium–oxygen batteries and a direct comparison with the analogous sodium systems. The general properties, major benefits and challenges, recent strategies for performance improvements and general guidelines for further development are summarized and critically discussed. In general, the substitution of lithium for sodium has a strong impact on the overall properties of the cell reaction and differences in ion transport, phase stability, electrode potential, energy density, etc. can be thus expected. Whether these differences will benefit a more reversible cell chemistry is still an open question, but some of the first reports on room temperature Na/S 8 and Na/O 2 cells already show some exciting differences as compared to the established Li/S 8 and Li/O 2 systems.